Organizational and legal regulation of the financial sector of the economy amid European integration - Федотов, Олексій Павлович; Федотов, О. П.; Федотов, Алексей Павлович; Fedotov, Oleksii P.; Левченко, Світлана Григорівна; Левченко, С. Г.; Левченко, Светлана Григорьевна; Levchenko, Svitlana H.; Levchenko, Svetlana (Baltija Publishing, 2018)
Financial sector development depends on the efficiency of its regulatory mechanisms that should correspond to the directions of implementation of state financial policy, which is aimed at the support for economic stability, protection of interests of participants in financial markets, and provision of rational use of growing financial market potential. Introduction of the mechanism of organisational and legal regulation is able to implement a complex approach to the application of various methods, means, other regulators on processes of effective formation and use of state financial resources in order to ensure their coordination and correspondence to strategic development priorities of the state. The purpose of the article is to substantiate features of organisational and legal regulation of the financial sector of the economy of EU countries and Ukraine, identify the main directions for reformation and recommendations for its improvement in the context of European integration trends and the possibility of securing competitive positions of Ukraine in the international market. The most widespread in the world are two models for regulating the financial sector’s activity – sectoral model and mega-regulator model. In the sectoral model, functions of public authorities are distributed according to three financial sectors (banking, insurance, stock). The model of mega-regulator determines the peculiarities of establishing a single authority endowed with functions of supervision and regulation of the financial sector. At the modern state of countries’ development, the main methods and forms of state regulation of the financial sector are determined by direct (development and adoption of laws and regulations, licensing of the activities, supervisory activities and implementation of measures of supervision of financial institutions) and indirect (changes in the volume of cash resources, securities issue, interest policy, provision of guarantees on fulfilment of obligations for securities of separate issuers, encouragement of foreign relations with international financial organisations) influence. Financial sector regulation in the EU and Ukraine is carried out according to the sectoral model where banking activities are subject to the Central Bank; activities in the market for securities are regulated by the National Securities and Stock Market Commission; activities of other financial intermediaries and financial companies are regulated by the National Commission for State Regulation of Financial Services Markets. Results of the research conducted allow determining the features of state regulation of the financial sector of the economy of Ukraine: the lack of legislative environment for regulating the financial status at the macrolevel and microlevel; provisions of the existing regulatory framework are aimed at the regulation of economic security; the absence of strategic benchmarks fixed in long-term documents for ensuring financial development of the country and the economic development of financial institutions; the presence of several regulators of the state of the financial system that duplicates functions and causes inefficient work; information closeness of regulators of financial market and financial system regarding the results of their work on ensuring the financial stability of the state. In order to improve rating positions and competitive advantages of Ukraine in global markets, it is necessary to develop additive legal framework and state support program for export-oriented enterprises for the promotion of export of finished products with high added value; start the policy of expansion on the basis of expansion of both geographical and commodity structure of exports.

Розвиток фінансового сектору залежить від ефективності його регуляторних механізмів, які мають відповідати напрямам реалізації державної фінансової політики, яка спрямована на підтримку економічної стабільності, захист інтересів учасників фінансових ринків, забезпечення раціонального використання зростаючого потенціалу фінансового ринку. Запровадження механізму організаційно-правового регулювання дозволяє реалізувати комплексний підхід до застосування різноманітних методів, засобів, інших регуляторів до процесів ефективного формування та використання державних фінансових ресурсів з метою забезпечення їх узгодженості та відповідності стратегічного розвитку пріоритетів держави. Метою статті є обґрунтування особливостей організаційно-правового регулювання фінансового сектору економіки країн ЄС та України, визначення основних напрямів реформування та рекомендацій щодо його вдосконалення в контексті євроінтеграційних тенденцій та можливості забезпечення конкурентихі позиціій України на міжнародному ринку. Найбільш поширеними у світі є дві моделі регулювання діяльності фінансового сектора – галузева модель і модель мегарегулятора. У галузевій моделі функції органів державної влади розподілені за трьома фінансовими секторами (банківський, страховий, фондовий). Модель мегарегулятора визначає особливості створення єдиного органу влади, наділеного функціями нагляду та регулювання фінансового сектору. За сучасного стану розвитку країн основні методи та форми державного регулювання фінансового сектору визначаються прямим (розробка та прийняття законодавчих та нормативно-правових актів, ліцензування діяльності, наглядова діяльність та здійснення заходів нагляду за фінансовими установами) і непрямим (зміна обсягу грошових ресурсів, випуск цінних паперів, процентна політика, надання гарантій виконання зобов'язань за цінними паперами окремих емітентів, заохочення зовнішніх зв'язків з міжнародними фінансовими організаціями) впливом. Регулювання фінансового сектору в ЄС та Україні здійснюється за галузевою моделлю, де банківська діяльність підпорядкована Центральному банку; діяльність на ринку цінних паперів регулюється Національною комісією з цінних паперів та фондового ринку; діяльність інших фінансових посередників та фінансових компаній регулюється Національною комісією, що здійснює державне регулювання у сфері ринків фінансових послуг. Результати проведеного дослідження дозволяють визначити особливості державного регулювання фінансового сектору економіки України: відсутність законодавчого середовища для регулювання фінансового стану на макро- та мікрорівні; положення існуючої нормативно-правової бази спрямовані на регулювання економічної безпеки; відсутність зафіксованих у довгострокових документах стратегічних орієнтирів забезпечення фінансового розвитку країни та економічного розвитку фінансових установ; наявність кількох регуляторів стану фінансової системи, що дублює функції та спричиняє неефективну роботу; інформаційна близькість регуляторів фінансового ринку та фінансової системи щодо результатів їхньої роботи щодо забезпечення фінансової стабільності держави. З метою покращення рейтингових позицій та конкурентних переваг України на світових ринках необхідно розробити адитивну законодавчу базу та програму державної підтримки експортоорієнтованих підприємств щодо стимулювання експорту готової продукції з високою доданою вартістю; розпочати політику розширення на основі розширення як географічної, так і товарної структури експорту.
Fedotov A. Organizational and legal regulation of the financial sector of the economy amid European integration / A. Fedotov, S. Levchenko // Baltic Journal of Economic Studies. - Vol. 4. - Issue 5. - Baltija Publishing, 2018. – P. 379-386.
Keywords: financial sector; state regulation; state supervision; legal framework; financial institutions; competitiveness; European integration; фінансовий сектор; державне регулювання; державний нагляд; правова база; фінансові інститути; конкурентоспроможність; євроінтеграція; Research Subject Categories::LAW/JURISPRUDENCE